1997
DOI: 10.1046/j.1365-2567.1997.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered interleukin‐2 receptor α‐chain is expressed in human T‐cell leukaemia virus type‐I‐infected T‐cell lines and human peripheral blood mononuclear cells of adult T‐cell leukaemia patients through an alternative splicing mechanism

Abstract: SUMMARYA polymerase chain reaction (PCR) method was used to detect the interleukin-2 receptor a-chain (IL-2Ra) chain which lacks the conventional transmembrane ( TM) domain in mRNA from human T-cell leukaemia virus type-I ( HTLV-I ) -infected cell lines or peripheral blood mononuclear cells (PBMC ) isolated from adult T-cell leukaemia (ATL) patients. Primer pairs encompassing the TM domain were selected to generate a 357-base pair (bp) fragment. A 146-bp PCR product was observed consistently in addition to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…The increased expression of pre-mRNA processing genes, such as SRPK1, and altered splicing of gene products may contribute to pathogenesis for some of the tumour. Notably, the altered splicing patterns of IL-2 receptor (Horiuchi et al, 1997), Fas (Sugahara et al, 1997), MEL1 (Yoshida et al, 2004) and HTLV-I pX genes (Berneman et al, 1992) were reported. Such alternative splicing events may be associated with the overexpression of SRPK1.…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of pre-mRNA processing genes, such as SRPK1, and altered splicing of gene products may contribute to pathogenesis for some of the tumour. Notably, the altered splicing patterns of IL-2 receptor (Horiuchi et al, 1997), Fas (Sugahara et al, 1997), MEL1 (Yoshida et al, 2004) and HTLV-I pX genes (Berneman et al, 1992) were reported. Such alternative splicing events may be associated with the overexpression of SRPK1.…”
Section: Discussionmentioning
confidence: 99%
“…The Δ4 protein isoform was further characterized by Neeper et al [47]: Unlike full-length CD25, the Δ4 isoform was incapable of binding IL-2. Horiuchi et al [48] also provided evidence for another alternatively spliced mRNA from IL2RA encoding an isoform lacking the amino acids encoded by exons 5 to 7, which includes the transmembrane region, and is presumably secreted.…”
Section: Il-2/il-2r Transcriptional Regulation: Splicingmentioning
confidence: 98%
“…Waldmann (20). The receptor is not expressed by resting normal cells while it is overexpressed by a proportion of abnormal cells of lymphoid neoplasia (21), including adult T-cell leukemia (22).…”
Section: Introductionmentioning
confidence: 99%